SIMPATIK website nutrition education on mother's knowledge and diversity of toddler consumption in Jambi City - Junita Junita; Rusmimpong Rusmimpong; Winda Triana; Egy Sunanda Putra (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The problem of under-five nutrition is still a significant concern in developing countries. One of the main factors is the level of nutritional knowledge, so feeding toddlers is inappropriate and less varied. Nutrition education must be delivered in an informative and flexible. This study aims to analyze the effect of nutrition education based on the SIMPATIK website on mothers' knowledge and diversity of toddler consumption in Jambi City. The study used a Quasy Experimental design in a pre-post test only, with 60 mothers of toddlers as subjects in the working area of the Tahtul Yaman Public Health Center in 2022. Were collection used a questionnaire, interviews and assistance using the SIMPATIK. Statistical analysis using the Wilcoxon test at 95% CI. The results of the study, the SIMPATIK website on the nutritional knowledge of toddler mothers (p= 0,000; = 2,18), and diversity of food consumption (p= 0,000; = 0,99). In conclusion, SIMPATIK increased the nutritional knowledge of mothers of toddlers and the variety of toddlers' consumption in Jambi City. The SIMPATIK website can be used as a tool for nutrition education in the community.